2013
DOI: 10.1016/j.aos.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Classification situations: Life-chances in the neoliberal era

Abstract: a b s t r a c tThis article examines the stratifying effects of economic classifications. We argue that in the neoliberal era market institutions increasingly use actuarial techniques to split and sort individuals into classification situations that shape life-chances. While this is a general and increasingly pervasive process, our main empirical illustration comes from the transformation of the credit market in the United States. This market works as both as a leveling force and as a condenser of new forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
217
1
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(233 citation statements)
references
References 52 publications
1
217
1
14
Order By: Relevance
“…Another way to identify the consequences of the financialization of daily life is to show the inequalities of what Fourcade and Kieran (2013) call "life chances". While Georges Gloukoviezoff (2010) showed that access to financial products and skills in using them are indispensable to social life in France as elsewhere, there are no quantified measures that prove the connections between difficulty in accessing financial products and social success -partially because it is very difficult to obtain bank data in these areas.…”
Section: The Role Of Finance In French Household Budgetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to identify the consequences of the financialization of daily life is to show the inequalities of what Fourcade and Kieran (2013) call "life chances". While Georges Gloukoviezoff (2010) showed that access to financial products and skills in using them are indispensable to social life in France as elsewhere, there are no quantified measures that prove the connections between difficulty in accessing financial products and social success -partially because it is very difficult to obtain bank data in these areas.…”
Section: The Role Of Finance In French Household Budgetsmentioning
confidence: 99%
“…One part of the literature on financialization describes the inequalities that it produces: not only is it the source of tremendous income inequality (Godechot, 2016;Atkinson et al, 2011), but others have shown that with equal income, having chosen savings and insurance products well, together with having a good credit score can have very different effects on accumulated wealth (Fourcade and Kieran, 2013). While some researchers adopt a critical position in response to these manufactured inequalities, an entire current support that the promotion of financial literacy takes the central role of financial choices in social life for granted and considers it necessary to transform the behavior of individuals in order for them to understand the risks they bear (Lusardi and Mitchell, 2011).…”
mentioning
confidence: 99%
“…Standards and classifications order entities by locating them within specific categorical systems, but in doing so they also enact associations and dissociations, relations of similarity and relations of difference. This is visible in the recent work by Fourcade and Healy (2013), whose Weberian-inspired analysis of classification situations points at how infrastructures-from credit scoring systems to crowdsourced mechanisms for wine rating-operate as distributed sieves that sort people, things, and evaluations along specific orders of worth-infrastructures facilitate this type of classification situations by making them durable and naturalized. Indeed, the construction of a stable reality for market actors is necessarily predicated on the infrastructural work carried out by others: what is second nature to those involved in a transaction, what is obviously and blatantly a "meaningful relation" for parties to an exchange, is some other actor's rebuttable convention (Boltanski and Thevenot 1999) of counting, ordering, and technical interoperability.…”
Section: Transactions That Mattermentioning
confidence: 97%
“…These words are loaded not only with moralizing assumptions, but also with racial understandings about who gives charity, to whom, and why; who is innocent and who is guilty; who is corrupt and who is maximizing their potential; who is neutral and who is biased; which communities need development and growth; and why redistribution is not an alternative. In contemporary society, under the process of financialization I noted above, abstracted financial concepts from credit scores (Fourcade & Healy, 2013) to stock valuations to derivatives' crystal-ball predictions (Martin, 2013), carry increasing material weight and consequences-but our complex algorithms are still premised on racial stereotypes and ideologies (for one possible mechanism, see Soss, Fording, & Schram, 2008's "Racial Classification Model").…”
Section: The Social Life Of Economic Termsmentioning
confidence: 99%